Onward : how Starbucks fought for its life without losing its soul - Schultz, Howard; Gordon, Joanne (New York, NY : Rodale : Distributed to the Trade by Macmillan, 2011)
In 2008, eight years after stepping down as Starbucks' CEO, Schultz returned to oversee the company's operations during a moment in history that left no company unscathed. "Onward" tells the remarkable story of Schultz's return and the company's ongoing transformation
pt. 5. Courage. Innovate -- Conviction -- Connecting dots -- Balance -- Conscience -- Winning -- Ni hao
Includes index
Keywords: Schultz, Howard; Starbucks Coffee Company; Coffee industry -- United States; Coffee -- United States -- Marketing; Organizational change -- United States; Leadership -- United States; Marketing; Industries; Coffee drinks; Organizational change; Leadership; Marketing; Industry; Coffee; Organizational Innovation; Leadership; United States